Original paperImpact of diabetes on in-hospital and long-term mortality in patients with acute myocardial infarction treated with coronary angioplasty - Tomaszuk-Kazberuk, Anna; Kożuch, Marcin; Bachórzewska-Gajewska, Hanna; Małyszko, Jolanta; Dobrzycki, Sławomir; Kosacka, Urszula; J. Musiał, Włodzimierz (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2011)
Introduction : Diabetes (DM) has been recognized as a strong predictor of high mortality and morbidity in patients after acute myocardial infarction (AMI). Various studies have shown that the low rate of invasive strategy may influence this situation. Aim : To assess the influence of DM on in-hospital and long-term mortality and morbidity in patients with AMI treated invasively. Material and methods : Nine hundred and eighty-four patients with AMI (both ST-segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction) treated with percutaneous coronary intervention (PCI) were divided into 2 groups according to the presence of DM. Total mortality and MACE were evaluated during 682.4 ±229.8 day follow-up. Results : We enrolled 286 women and 698 men, mean age 65 ±11 years. Diabetes was present in 189 patients (19.2%). The patients with DM were older (66.1 ±11.3 years vs. 63.2 ±11.7 years, p = 0.0022), had higher body mass index (29.8 ±7.3 kg/m 2 vs. 27.7 ±4.9 kg/m 2 , p < 0.00001), more often hypertension (79% vs. 61%, p < 0.00001), lower HDL cholesterol (45.2 ±14.6 vs. 42.4 ±12.2, p = 0.022) and triglycerides (146.4 ±184.5 vs. 120.1 ±93.6, p = 0.009). There were no significant differences in the extent of coronary artery disease. The incidence of in-hospital major adverse cardiac events and all-cause mortality was similar in both groups (p = 0.075 and p = 0.649), while after a follow-up of 24 months significantly greater mortality rate for diabetics was observed (9% vs. 15%, p = 0.0294). All other end-points occurred with similar frequencies. In multivariate analysis the following parameters correlated with death: age, systolic RR and glycaemia on admission. Conclusions : Diabetes had no negative effect on in-hospital mortality after an acute MI treated with PCI. At 2-year follow-up rates of death were significantly higher in patients with DM compared to those without diabetes. The presence of DM was not associated with significantly increased morbidity as compared to non-diabetic patients.